Art and cosmotechnics - Hui, Yuk, 1985- (E-flux journal (Series), 2021)
"Art and Cosmotechnics addresses the challenge of technology to the existence of art and traditional thought, especially in light of current discourses on artificial intelligence and robotics"-- Provided by publisher.